The educational body in the legitimate schools of Damascus in the eleventh century AH/seventeenth century AD (Damascus University Journal of Historical Studies, 2022)
This research sheds light on the educational bureau at Damascus’ religious schools in the Eleventh century (Hijri) / Seventeenth century, which included the educational man, who is responsible for educating children in closed sessions (Ktatib). And the other educational man who is responsible for repetition of the lessons at schools. And the deputy teacher who substitute the absent teacher. The teacher is the most important figure in the teaching process who has been restricted to a set of conditions and duties that characterize his career at school. Appointing teacher was strict to the involved Othman’s authority. The teachers have followed many illegal or indirect ways to get their positions as teachers as bribery and travelling to the capital city for begging the authentic people who are in charge or paying bribery as well as to use personal affairs to get this chance. Many competitions between teachers were taking place to get the chance of teaching at schools. The teachers’ ages were different as they got appointed at schools as well as their salaries. Teacher at that time didn’t got enough with one scientific position at school, but they occupied more than one position. Moreover, schools hosted students and specially the envoy students (students with scholarship). The research assured that the educational organizations of Damascus schools with other Othman Empire educational institutions formed an old Islamic center for jurisprudence.
Keywords: The educational body in the legitimate schools of Damascus in the eleventh century AH/seventeenth century AD